"¿Como vamos?", a tool to support indigenous women's participation in the governance of their territories in the Peruvian Andes and Amazon - CGIAR Research Program on Policies, Institutions, and Markets (2020)
"¿Como vamos?" was piloted with four organizations affiliated to ONAMIAP. ONAMIAP has requested support to implement it in its workshops.